2016
DOI: 10.1080/13816810.2016.1227454
|View full text |Cite
|
Sign up to set email alerts
|

Association of single-nucleotide polymorphisms in non-coding regions of the TLR4 gene with primary open angle glaucoma in a Mexican population

Abstract: We have identified intronic TLR4 SNPs as genetic susceptibility alleles for POAG in a Mexican population. Our findings support the association of the TLR4 gene with POAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
0
17
1
2
Order By: Relevance
“…However, the present study did not find any significant association of rs11536889 and rs7873784 with POAG risk after adjusting for covariates. Some studies concluded that TLR4 SNPs were positively associated with POAG risk, 18,19 although negative results also were reported 16,17 Several limitations should be noted with respect to the present study. 27,28 Previous population studies have begun to report the relationship between TLR4 gene polymorphism and POAG, although the conclusions of these studies are inconsistent.…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…However, the present study did not find any significant association of rs11536889 and rs7873784 with POAG risk after adjusting for covariates. Some studies concluded that TLR4 SNPs were positively associated with POAG risk, 18,19 although negative results also were reported 16,17 Several limitations should be noted with respect to the present study. 27,28 Previous population studies have begun to report the relationship between TLR4 gene polymorphism and POAG, although the conclusions of these studies are inconsistent.…”
Section: Discussioncontrasting
confidence: 54%
“…27,28 Previous population studies have begun to report the relationship between TLR4 gene polymorphism and POAG, although the conclusions of these studies are inconsistent. Some studies concluded that TLR4 SNPs were positively associated with POAG risk, 18,19 although negative results also were reported 16,17 . A study by Mousa et al 16 suggested no association between genotypes or allele of rs4986791 in the TLR4 gene and POAG.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations